Comparison between Nanosecond Pulse and Direct Current Electrocoagulation for Textile Wastewater Treatment - Que Ho Nguyen (Journal of Water and Environment Technology, 2020)

(untitled)
This paper proposes the utilization of a nanosecond pulsed (NSP) power supply in the electrocoagulation (EC) system for textile wastewater treatment. Four aluminum plates arranged in a monopolar-parallel configuration are utilized as electrodes in a 200 ml EC reactor. Chemical oxygen demand (COD) and specific energy consumption (SEC) are utilized to characterize the performance of NSP-powered EC. A DC power supply is considered as a benchmark. Field-emission scanning electron microscopy, X-ray diffraction, and energy-dispersive spectroscopy are utilized to characterize flocs. The results reveal that a maximum COD removal efficiency of 77% can be achieved by utilizing NSP power, while a value of only 60% can be achieved by utilizing DC power. Additionally, NSP power consumes at least 24% less energy than DC power at a similar COD removal efficiency. The utilization of NSP power for textile wastewater treatment allows for high COD removal efficiency with a significantly lower SEC compared to traditional DC-powered EC. It is believed that the low SEC exhibited by NSP power could be useful for promoting the utilization of EC for wastewater treatment and could contribute to the reduction of the carbon footprint of this process.